Knowledge Among Women at Reproductive Age About Intrauterine Device in Baquba City (Medico Legal Update, 2021)
Background: The intrauterine device (IUD) is the most popular form of reversible long-acting contraceptionin the world which is inserted into a woman›s uterus to prevent pregnancy.Objectives: To study knowledge among women at reproductive age about intrauterine device in baqubacity. Subjects and Method: a cross-sectional study was conducting among women at reproductive age whoattended outpatient clinics of Al-Batool Teaching Hospital in Baquba City from the period of the 1st ofJanuary to the 30th of June 2020.Results: Among 900 women who included in this study, with mean age about 32.2±8 years old, about77.1% of women respondents had poor knowledge about this method of birth control. The knowledge scorewas affected significantly by level of education, age, residency, occupation, years of marriage, number ofparity as well as the use of IUD. The main source of information is friends and relatives who represent about93.3% and a limited role of health care providers. This may cause negative beliefs as well as many mythsand rumors about IUD. Conclusion: in this study women were unaware about the basic knowledge of IUDs.